Survey of the readiness of Physical Education, Sports, and Health teachers in implementing the Emancipated Curriculum at the education unit level of Senior High School - Bagus Nur Andika Putra; Risfandi Setyawan; Basuki Basuki (Sriwijaya Journal of Sport, 2024)
Background Problems: Physical Education (PE) teachers play an important role in realizing holistic learning that supports the formation of students' characters and skills by the Pancasila learner profile. The implementation of an Emancipated Curriculum provides opportunities for teachers to be more flexible in designing learning but presents challenges such as understanding the concept of the curriculum, the ability to design competency-based learning and limited supporting facilities. Research Objectives: This study aims to analyze the readiness of PE teachers to implement the Emancipated Curriculum (Kurikulum Merdeka) at the senior high school level. Methods: his research employs a quantitative method with a descriptive survey design. The participants consist of 12 PE teachers selected using purposive sampling techniques. Data were collected using a Likert-scale-based questionnaire covering three main aspects: understanding of the Emancipated Curriculum, ability to design learning plans, and utilization of supporting facilities. Results: The findings reveal that overall, PE teachers' readiness falls into the "Moderately Ready" category, with the highest average score in understanding the Emancipated Curriculum (3.25), followed by the ability to design learning plans (3.05), and the utilization of supporting facilities (2.85). The main challenges faced by teachers include limited supporting facilities and insufficient intensive training related to Emancipated Curriculum learning strategies. Conclusion: In conclusion, while PE teachers demonstrate enthusiasm for implementing the Emancipated Curriculum, there is an urgent need to enhance training and provide adequate facilities. The study recommends organizing continuous training programs, mentoring sessions, and the provision of sufficient resources to support the successful implementation of the Emancipated Curriculum.